Między cywilizacją a naturą – przedmioty nie/codziennego użytku w powieści Marlen Haushofer Ściana - Głuszko-Boczoń, Estera (Przestrzenie Teorii, 2025)
Marlen Haushofer’s novel The Wall (1963) has been well received by readers and critics in Germanspeaking countries and beyond. Owing to a mysterious decree of fate, the heroine is separatedfrom the external world by an invisible barrier—the wall. From then on, her life is focused on it. She is forced to live in complete seclusion and adapt to an unusual everyday life in which items also play an important role. Some prove very useful, some utterly useless. Yet they allow the main character to put some order in the new reality and reassess her relationship to her own role in the world, both before and after the catastrophe.